Student Perceptions of Video Tutorials: Quality and Usefulness in Learning Educational Statistics - Yudi Pratama; Dios Sarkity (Jurnal Ilmiah Profesi Pendidikan, 2026)
The integration of digital technology in higher education has encouraged the use of innovative learning media, including video tutorials, to support students’ understanding of complex subjects such as educational statistics. This study aims to analyze students’ perceptions of the quality and usefulness of video tutorial–based learning in data processing using Microsoft Excel and SPSS. This research employed a descriptive quantitative approach with a survey design involving 90 students who had completed the Educational Statistics course. Data were collected using a 30-item questionnaire covering five indicators: material relevance, learning effectiveness, video media quality, accessibility, and learning motivation. The data were analyzed using descriptive statistics in the form of percentages. The results showed that students’ perceptions were categorized as very good across all indicators, with accessibility obtaining the highest score (90.59%), followed by video media quality (90.48%), material relevance (90.07%), learning effectiveness (89.15%), and learning motivation (89.07%). The majority of students’ scores ranged from 80% to 100%, with an average between 88% and 90%. In conclusion, video tutorial–based learning is perceived as highly useful and of high quality in supporting students’ learning experiences in educational statistics, particularly in data processing using Excel and SPSS. Therefore, this method can be considered an effective alternative learning strategy, although it should be combined with interactive approaches to further enhance student motivation.